تحریک ِہجرت:علامہ اقبالؒ اور امام احمد رضاؒ: Migration Movement: Allama Iqbal and Imam Ahmad Riza - ڈاکٹر گل احم, (Tashkeel e Jadeed, 2023)
After the failed war of independence in 1857, the Muslims in the subcontinent developed political consciousness a little later than the Hindus. Thanks to the educational movement of Sir Syed, the understanding of the new political system was created, but the conservative class was still incapable of this political consciousness. Therefore, the nationalist scholars started many movements without wisdom and vision. These include the Khilafat movement, the Turk-Mowalat movement and the Hijrat movement. Among them, the Hijrat movement is particularly noteworthy. A fatwa was given that India has become a war center, so all Muslims should migrate from here. Imam Ahmad Raza and Allama Iqbal raised their voices against this fatwa. Maulana Ahmad Raza did not want to withdraw from India under any circumstances and Iqbal was also aware of the harmful effects of this movement, so these two thinkers strongly opposed this movement and played an important role in failure of this movement, in this paper the position of two thinkers of this movement has been examined.